Association of demographic, geographic, and economic factors of countries with the number of medals won in table tennis at the European Championships - Metikoš, B.; Špehar, N.; Milanovic, M.; Perinovic, V. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
This study researched the association between the number of medals won in table tennis, at European Championships, over the past 30 years, with geographic (country size), demographic (population), and economic (GDP per capita) factors. It has shown that there are no statistically significant associations between the criterion and dependent variables. However, the only statistically significant correlation was observed between the size of the country and the population variables. Although countries with a larger population have a larger selection base for athletes, those with higher GDP per capita have the potential to provide greater financial resources for sports programs, equipment, infrastructure, coaches as well as training programs that can improve the development and success of table tennis athletes. Nevertheless, this analysis has not confirmed these hypotheses. It should be noted that other factors influence athletic achievement. Persistence, motivation, the composition of a competition and its organization system, as well as investment in quality coaching staff, can be key for the development of young talents and achieving record achievements, as well as the tradition and recognition of a sport in a particular country.